Identifying Potential Classification Criteria for Calcium Pyrophosphate Deposition Disease: Item Generation and Item Reduction. Issue 10 (30th June 2022) - Tedeschi, Sara K.; Pascart, Tristan; Latourte, Augustin; Godsave, Cattleya; Kundakci, Burak; Naden, Raymond P.; Taylor, William J.; Dalbeth, Nicola; Neogi, Tuhina; Perez‐Ruiz, Fernando; Rosenthal, Ann; Becce, Fabio; et al.
Abstract : Objective: Classification criteria for calcium pyrophosphate deposition (CPPD) disease will facilitate clinical research on this common crystalline arthritis. Our objective was to report on the first 2 phases of a 4‐phase process for developing CPPD classification criteria. Methods: CPPD classification criteria development is overseen by a 12‐member steering committee. Item generation (phase I) included a scoping literature review of 5 literature databases and contributions from a 35‐member combined expert committee and 2 patient research partners. Item reduction and refinement (phase II) involved a combined expert committee meeting, discussions among clinical, imaging, and laboratory advisory groups, and an item‐rating exercise to assess the influence of individual items toward classification. The steering committee reviewed the modal rating score for each item (range –3 [strongly pushes away from CPPD] to +3 [strongly pushes toward CPPD]) to determine items to retain for future phases of criteria development. Results: Item generation yielded 420 items (312 from the literature, 108 from experts/patients). The advisory groups eliminated items that they agreed were unlikely to distinguish between CPPD and other forms of arthritis, yielding 127 items for the item‐rating exercise. Fifty‐six items, most of which had a modal rating of +/– 2 or 3, were retained for future phases. As numerous imaging items were rated +3, the steering committee recommended focusing on imaging of the knee and wrist and 1 additional affected joint for calcification suggestive of CPP crystal deposition. Conclusion: A data‐ and expert‐driven process is underway to develop CPPD classification criteria. Candidate items comprise clinical, imaging, and laboratory features.